(Trans-Multi)Culturally Responsive Mathematics: (Re)Creating Spaces for Loving Kindness - Raisinghani, Latika (Journal of the Canadian Association for Curriculum Studies, 2021)
In this paper, I relive my experiences of (un)learning, (re)learning and (re)searching mathematics in multiple cultural contexts. I begin by recounting the moments of dilemma that many students encounter in various cultural contexts, which inspired me to weave the threads of (trans-multi)culturally responsive mathematics. I share this story through the narratives, poems and digital postcards that I created in my auto-ethnographical life writing of engaging in (re)learning of and with(in) mathematics. Underlying these efforts and actions is the hope that sharing these may help in creating spaces for inviting (trans-multi)culturally responsive mathematics in contemporary diversity-rich classrooms. Informed by critical and transformational multicultural education perspectives and the insights of key curriculum scholars—Aoki, Pinar, Schwab, Leggo and Noddings—a (trans-multi)culturally responsive mathematics is a calling for teachers to acknowledge mathematics as a human endeavour. It is an initiation to invite student’s lived experiences and multiple ways of knowing in mathematics classrooms with relational caring and loving kindness. Aiming to educate diverse students in a socially-just manner, a (trans-multi)culturally responsive mathematics urges teachers to embrace wholistic teaching that not only focuses on the mind and body, but also strives for educating the heart and spirit. Thus, it is an ethical, intellectual, political and relational inquiry, which critically engages students with mathematics to discover what knowledge is most worth within and beyond the boundaries of classroom(s) and thereby empowers them to co-create mathematics that is living.